Efeito fundador em populações de cativeiro: o caso do urso de óculos (Tremarctos ornatus Cuvier, 1825) e seu significado para o manejo e futura conservação ex situ - Corrêa, Mariana Coletto (2014)
Species kept in captivity are of great importance for in situ conservation of natural populations. In order to fulfill this role, they need to be properly managed with the aim to avoid the consequences of a captive environment, such as: loss of genetic diversity, inbreeding depression, accumulation of deleterious alleles and genetic adaptation to captivity (the first three due to the small number of breeding stock). Thus, with the aim to test founder effects in captive ―populations‖, we used as study model the spectacled bears from Brazilian zoos. This ―population‖ consists of twenty-one bears found in eight zoos along the country, which are originated from just twelve founding individuals. To test a possible founder effect, we analyzed twelve heterologous microsatellite loci for all the specimens of the species in Brazil. Results for the number of alleles and allelic richness obtained through the rarefaction method showed that spectacled bears in captivity have reduced levels of allelic richness in relation to three natural populations (Colombia, Ecuador and Venezuela) studied by other authors; suggesting that bears from Brazilian zoos suffered the consequences of a founding effect, as they have only a fraction of the gene pool of the ancestral population. From the information present in the studbook was possible to verify that there are two families of spectacled bears, and according to the individuals´s multilocus genotypes, we found alleles that are present in a same family and absent in the other. Regarding the kinship, there was a discrepancy in the results with the molecular estimators through the softwares ML-Relate and Coancestry and the information given by the institutions. The information obtained in this work are fundamental to the ex situ conservation program in Brazil with the objective of maintain as high as possible the genetic diversity for future reintroduction plans of the species in nature.